(untitled) (Bangladesh Journal of Medical Science, 2016)
Background: Metabolic syndrome (MS) constitutes the clustering of clinical and biochemical risk factors, which are associated with increased risk of cardiovascular events. Non ST elevation myocardial infarction (NSTEMI) accounts for the important part of acute coronary syndrome (ACS) with considerable morbidity and mortality. The aim of this study was to investigate the association of MS with angiographic severity of coronary artery disease (CAD) in patients with NSTEMI. Methods: This study included 192 prospectively enrolled NSTEMI patients. The patients underwent coronary angiography (CAG). CAG were evaluated via Sullivans method. Results: Statistically significant difference in vessel score observed, such that higher triple vessel disease (TVD) in MS patients (42.7% vs. 15.6%, p<0.001) and single vessel disease (SVD) in patients without MS (45.8% vs. 21.9%, p<0.001). Patients with MS had higher mean total stenosis score (9.26±4.29 vs. 6.06±3.07, p<0.001) and mean extension score (53.70±18.11 vs. 39.11±17.59, p<0.001). Correlation analysis found direct correlation between angiographic scores and MS scores, total cholesterol, LDL-C, HDL-C, TG and waist circumference. Individual components of MS were independent predictors of high total stenosis score and extension score on multivariate linear regression analysis. Conclusion: Metabolic syndrome, as well as, individual components of MS was independently associated with angiographically severe CAD. Bangladesh Journal of Medical Science Vol.15(4) 2016 p.511-516